Assessment of genetic factors for type 2 diabetes mellitus - Yamada, Yoshiji; Matsuo, Hitoshi; Segawa, Tomonori; Watanabe, Sachiro; Kato, Kimihiko; Kameyama, Takashi; Yokoi, Kiyoshi; Ichihara, Sahoko; Metoki, Norifumi; Yoshida, Hidemi; Satoh, Kei; Nozawa, Yoshinori (International journal of molecular medicine, 2006)
The purpose of the present study was to identify gene polymorphisms for reliable assessment of genetic factors for type 2 diabetes mellitus. The study population comprised 4853 unrelated Japanese individuals (2688 men, 2165 women), including 1489 subjects with type 2 diabetes mellitus (969 men, 520 women) and 3364 controls (1719 men, 1645 women). The genotypes for 148 polymorphisms of 124 candidate genes were determined with a method that combines polymerase chain reaction and sequence-specific oligonucleotide probes with suspension array technology. Sixteen polymorphisms were related (p<0.05) to the prevalence of type 2 diabetes mellitus as determined by the chi-square test. Multivariable logistic regression analysis with adjustment for age, sex, and the prevalence of smoking revealed that, among these polymorphisms, the -603A↷G polymorphism of the gene for coagulation factor III (F3) was significantly (p<0.001) associated with the prevalence of type 2 diabetes mellitus, with the -603G allele representing a risk factor for this condition. A stepwise forward selection procedure demonstrated that F3 genotype (GG versus AA + AG) significantly (p<0.001) and independently affected the prevalence of type 2 diabetes mellitus. Genotype for F3 may prove reliable for assessment of genetic factors for type 2 diabetes mellitus. Determination of the genotype for this gene may contribute to personalized prevention of this condition.